2006
DOI: 10.1021/jf053048a
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potentials of Flaxseed by in Vivo Model

Abstract: The present study reports the antioxidant activity of flaxseed as measured by feeding weanling albino rats with 5.0% and 10.0% of flaxseed (constituting approximately 0.75 and 1.5 g kg(-)(1)) for 14 days followed by challenging animals with 2.0 g kg(-)(1) b.w. CCl(4) as toxin. Activity was assessed by measuring hepatic marker enzymes like catalase, superoxide dismutase (SOD), and peroxidase and comparing with those from the normal group and from a group receiving toxin without flaxseed. Treatment of CCl(4) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 43 publications
7
42
0
5
Order By: Relevance
“…Flaxseed hulls are rich in plant lignans, which are recognised as strong antioxidants (Prasad, 2000). They enhance endogenous level response by upregulating the expression of genes encoding the enzymes such as superoxide dismutase, catalase and peroxidase (Rajesha et al, 2006). Our recent results (Petit et al, 2009) have also shown that flaxseed hulls increase the activity of the enzyme superoxide dismutase in the mammary gland that is responsible for the removal of free radicals leading to oxidative stress.…”
Section: Fas Antioxidants and Reproductive Performancementioning
confidence: 94%
“…Flaxseed hulls are rich in plant lignans, which are recognised as strong antioxidants (Prasad, 2000). They enhance endogenous level response by upregulating the expression of genes encoding the enzymes such as superoxide dismutase, catalase and peroxidase (Rajesha et al, 2006). Our recent results (Petit et al, 2009) have also shown that flaxseed hulls increase the activity of the enzyme superoxide dismutase in the mammary gland that is responsible for the removal of free radicals leading to oxidative stress.…”
Section: Fas Antioxidants and Reproductive Performancementioning
confidence: 94%
“…[8,9] SDG, via various in vivo and in vitro studies was found to be a potential antioxidant agent. [10][11][12] It also appears to be effective against breast and colon cancer, [13] hyper cholesterolemic atherosclerosis, diabetes, [14] lupus nephritis, immune and inflammatory reactions. [15,16] In addition, SGD is found to possess a good antibacterial activity against gram positive and negative bacterial species.…”
Section: Synthesis Of 23-bis(34-dimethoxybenzyl)butane-1 4-diol (4)mentioning
confidence: 99%
“…In comparison to the previous techniques for determining xanthophylls in egg yolk samples [18][19][20], the procedure used in this study is an easy and small-scale technique that minimizes organic solvent consumption in the preparation of AX, CX, and ACAEE. The extract obtained by the extracting operation was purified by subsequent centrifugal monolithic silica spin mini-column, MonoSpin ® -SI.…”
Section: Sample Preparation-application Of Centrifugal Spin Mini-columnmentioning
confidence: 99%
“…Without regard for industrial nations and developing countries, the optimal harmonized method for chemical monitoring in foods must be simple, small scale, economical in time and cost, and must cause negligible harm to the environment and analysts. Several techniques based on high-performance liquid chromatography (HPLC) for the quantification of xanthophylls in egg yolk samples have been reported [18][19][20][21]. However, these methods cannot detect simultaneous AX, CX, and ACAEE; and they involve several analytical steps in the sample preparation, which are time-and cost-consuming and do not permit the determination of a large number of samples.…”
Section: Introductionmentioning
confidence: 99%